Analisis Sisa Hasil Usaha (SHU) sebagai Indikator Kinerja Koperasi Simpan Pinjam Tani Karya Bhakti - Khalimatus Sa'diyah; Anjani I'anatul Maula; Suwanda Eka Aprilia; Sayyidah Fadhilatun Nizzwah; Muhammad Ari Mukti; Ahmad Fadoil Alqoroni (LPPM Universitas Koperasi Indonesia, 2026)
This research aims to analyze the development of the Remaining Business Results (Sisa Hasil Usaha/SHU) of Koperasi Simpan Pinjam (KSP) Tani Karya Bhakti in Pacitan, East Java, as a key performance indicator and to identify its fluctuation trends from 2014 to 2024. The study employs a descriptive research method with a documentation study approach. Secondary data was gathered from the official database of the Department of Cooperatives and SMEs of East Java Province, covering SHU reports within the specified period. Data analysis was conducted using both trend analysis and qualitative descriptive techniques. The findings reveal that the SHU of KSP Tani Karya Bhakti exhibited a fluctuating pattern with a long-term upward trend. A significant peak occurred in 2016 (Rp14,730,900), followed by a sharp decline in 2020 (Rp5,205,500) due to the impact of the Covid-19 pandemic. Recovery was observed in 2021 and 2022, although a slight decrease occurred again in 2024. These fluctuations were primarily influenced by business volume, operational efficiency, and asset management. In conclusion, the cooperative's performance is categorized as fairly good because it consistently generates a positive SHU annually, despite the lack of stability. The study recommends that the cooperative improve operational efficiency and resource optimization to achieve more consistent growth.